An evaluation of nivolumab for the treatment of metastatic renal cell carcinoma. (3rd June 2018) - Zarrabi, Kevin; Wu, Shenhong
ABSTRACT: Introduction : The treatment paradigm for metastatic renal cell carcinoma (mRCC) has undergone a revolution with the rapid market approval of multiple agents over a three-year period. The immunogenicity of renal cell carcinoma (RCC) provided the biological rationale to assess the clinical efficacy of nivolumab, an immune checkpoint inhibitor. Nivolumab is approved for second-line treatment after failure of angiogenesis-targeted therapy and in combination therapy with ipilimumab for previously untreated intermediate- or poor-risk advanced RCC. Areas covered : The authors review the preclinical and clinical data supporting nivolumab employment in mRCC. Discussion of the underlying mechanisms of immunotherapy, data on objective responses, safety and tolerability, regulatory affairs, and future directions of nivolumab therapy are highlighted. Expert opinion : Nivolumab serves as a proof-of-principle of the efficacy of immunotherapy with checkpoint inhibition in mRCC. Nivolumab may be considered the leading monotherapy in the second-line setting for patients with low tumor volume considering its risks and benefits. Nivolumab was recently approved in the first-line setting as part of combination therapy with another immune modulator. Moreover, nivolumab use may offer clinicians the option for treatment beyond progression as emerging data has indicated possible overall survival benefits in this setting. Ongoing clinical studies may result in nivolumab use in the first-line setting, as monotherapy or in combination therapy with antiangiogenesis agents.